Digital Currency and Monetary Policy in Islamic Economics: Can Central Bank Digital Currencies (CBDCs) Be Islamically Compliant - Sofiana, Ratna; Utama, Satria (Yayasan Darussalam Bengkulu, 2025)
Background: This study aims to systematically evaluate whether Central Bank Digital Currencies (CBDCs) can be structured in compliance with Islamic monetary and financial principles, particularly addressing prohibitions of riba (usury) and gharar (excessive uncertainty). Method: A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, analyzing 47 peer-reviewed studies from Scopus, Web of Science, and Islamic economics journals (2015-2025) Results: The review finds that conventional interest-bearing CBDCs are non-compliant. However, a zero-return, 100% reserve-backed CBDC operating under wadiah (safekeeping) or qard (loan) contracts is widely permissible. Additionally, smart contract integration can automate zakat collection and qard al-hasan distribution, supporting Islamic monetary policy goals. Conclusion: This systematic literature review finds that a Shariah-compliant CBDC is theoretically possible within narrow design parameters, but the gap between conceptual compliance and operational Islamic monetary policy remains wide.